(untitled) (KULT_online, 2012)
The essays in Sabine Coelsch-Foisner and Sarah Herbe’s collection From the Cradle to the Grave explore the interrelation between human life-course models and their representation in literary genres from the renaissance to postmodernism. The volume thus ties in with current debates around literature and science, posthumanism, and especially the emergent field of age studies. By highlighting the significance of genre in the representation of the human life course, the book makes an important contribution to this field, yet it doesn’t provide a consistent theoretical framework for such discussions.